Designing an Auto Cropping Application System for Fish Eye Image Using the Edge Detection Method - Brian Sulu; Jullia Titaley; Luther A. Latumakulita; Altien J. Rindengan (Sam Ratulangi University, 2019)
Indonesia is one of the largest archipelagic countries in the world with the ocean area is larger than the mainland. This potential provides a great opportunity to do research in the maritime sector. The purpose of this research is to develop the application system that can automatically recognize and separate the fisheye images using the edge detection method. By using 20 fish digital images which taken by digital camera, the application system can recognize and separate the fisheye characteristic features with a good accuracy of 90%.